The need for social network analysis for the investigation of affective variables in second language acquisition - Wang, Mengzhong (Frontiers in Psychology, 2022)
Considering the inherent developmental nature of language learners’ affective variables (e.g., their motivation, grit, foreign language enjoyment, boredom), the nuances of the development of these constructs need to be approached from a Complex Dynamic Systems Theory (CDST) perspective. Among the qualitative research methodologies compatible with the CDST is the Social Network Analysis (SNA) with the interconnectedness and interdependence of systems within a social network at its core. In this paper, an overall introduction to SNA is presented first and then followed by a review of the limited existing literature in second language acquisition (SLA) studies. Then, I argue why this innovative research method is suitable to investigate the dynamic nature of L2 learners’ affective variables in the social network of classroom learning. I also suggest several relevant research questions that can potentially be formulated and answered using the SNA. The paper ends with conclusive remarks on the need for a more extensive use of innovative CDST-compatible research methods such as SNA in the prospective SLA line of research.